The role of the KIBRA and APOE genes in developing spatial abilities in humans - A. V. Kazantseva; R. F. Enikeeva; Yu. D. Davydova; R. N. Mustafin; Z. R. Takhirova; S. B. Malykh; M. M. Lobaskova; T. N. Tikhomirova; E. K. Khusnutdinova (Вавиловский журнал генетики и селекции, 2022)
In the contemporary high-tech society, spatial abilities predict individual life and professional success, especially in the STEM (Science, Technology, Engineering, and Mathematics) disciplines. According to neurobiological hypotheses, individual differences in cognitive abilities may be attributed to the functioning of genes involved in the regulation of neurogenesis and synaptic plasticity. In addition, genome-wide association studies identified rs17070145 located in the KIBRA gene, which was associated with individual differences in episodic memory. Considering a significant role of genetic and environmental components in cognitive functioning, the present study aimed to estimate the main effect of NGF (rs6330), NRXN1 (rs1045881, rs4971648), KIBRA (rs17070145), NRG1 (rs6994992), BDNF (rs6265), GRIN2B (rs3764030), APOE (rs7412, rs429358), and SNAP25 (rs363050) gene polymorphisms and to assess the effect of gene-environment interactions on individual differences in spatial ability in individuals without cognitive decline aged 18–25 years (N = 1011, 80 % women). Spatial abilities were measured using a battery of cognitive tests including the assessment of “3D shape rotation” (mental rotation). Multiple regression analysis, which was carried out in the total sample controlling for sex, ethnicity and the presence of the “risk” APOE ε4 allele, demonstrated the association of the rs17070145 Т-allele in the KIBRA gene with enhanced spatial ability (β = 1.32; pFDR = 0.037) compared to carriers of the rs17070145 CC-genotype. The analysis of gene-environment interactions revealed that nicotine smoking (β = 3.74; p = 0.010) and urban/rural residency in childhood (β = –6.94; p = 0.0002) modulated the association of KIBRA rs17070145 and АРОЕ (rs7412, rs429358) gene variants with individual differences in mental rotation, respectively. The data obtained confirm the effect of the KIBRA rs17070145 Т-allele on improved cognitive functioning and for the first time evidence the association of the mentioned genetic variant with spatial abilities in humans. A “protective” effect of the APOE ε2 allele on enhanced cognitive functioning is observed only under certain conditions related to childhood rearing.